Peer Assistance Strategy in the Management of Inclusion Students in Sawocangkring Elementary School - Tria Zuliatul Faiza; Istikomah Istikomah; Budi Haryanto (Proceedings of The ICECRS, 2020)
Inclusive schools are places for education for children with special needs who have the same rights as normal children. and learning in inclusive schools is one class without any difference. The purpose of this study was to determine peer assistance in managing students with special needs. The subjects of this study were 23 students at Sawocangkring Elementary School. This type of research is a descriptive qualitative method with an interactive approach. The results of this study are peers have a very important function in the development of attitudes, skills, socializing and peers can be used as peer tutors for children with special needs in explaining the material and accompany during breaks and other activities.